2019
DOI: 10.4085/1062-6050-350-17
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Among 3 Generic Patient-Reported Outcome Instruments in Patients With Lower Extremity Health Conditions

Abstract: Context Generic patient-reported outcome (PRO) instruments are designed to capture health-related quality-of-life outcomes and to determine treatment effectiveness from the patient's perspective. Multiple generic PROs are used in clinical practice, and an investigation of the psychometric properties of these instruments in a high-functioning, physically active population is important for the future use of these instruments. Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…For DIF analyses, a minimum of 200 subjects per group has been recommended. 38 In this study, we examined DIF with respect to age (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54), or 55+ years), sex, education (high school graduate or above, no high school diploma), race (White, non-White), ethnicity (Hispanic, non-Hispanic), and TBSA burned (0-19%, ≥20%). Differential item functioning analyses were conducted using ordinal logistic regression models with the lordif program in R (R Core Team 2016).…”
Section: Analysesmentioning
confidence: 99%
“…For DIF analyses, a minimum of 200 subjects per group has been recommended. 38 In this study, we examined DIF with respect to age (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54), or 55+ years), sex, education (high school graduate or above, no high school diploma), race (White, non-White), ethnicity (Hispanic, non-Hispanic), and TBSA burned (0-19%, ≥20%). Differential item functioning analyses were conducted using ordinal logistic regression models with the lordif program in R (R Core Team 2016).…”
Section: Analysesmentioning
confidence: 99%
“…These included the PROMIS-PF 20-item short form [10], OPUS-LEFS [12], and LEFS [15]. PROMIS-PF has been shown to have evidence of validity when tested with LLO users [25] and evidence of validity and/or reliability when tested with people diagnosed with a variety of health conditions that affect the lower extremities [26][27][28][29]. OPUS-LEFS has been shown to have excellent internal consistency when tested with a mixed sample of orthosis and prosthesis users [12].…”
Section: Methodsmentioning
confidence: 99%
“…The Patient‐Reported Outcome Measure Information System – Physical Function (PROMIS‐PF), is an IRT‐based item bank with a generic population focus 24 . PROMIS‐PF has been psychometrically evaluated with several clinical populations that often include LLO users, including people with lower extremity health conditions, 25 spine disorders, 26 ischemic stroke, 27 and multiple sclerosis 28 . Weber et al 29 tested PROMIS‐PF in a sample of 98 LLO users and reported initial evidence of known groups construct validity.…”
Section: Introductionmentioning
confidence: 99%